2012
DOI: 10.1007/s00784-012-0697-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a tin-containing fluoride mouth rinse on the bond between resin composite and erosively demineralised dentin

Abstract: The effect of a tin-containing fluoride mouth rinse on the bond between resin composite and erosively demineralised dentin Abstract Objectives: To evaluate the effect of a tin-containing fluoride (Sn/F) mouth rinse on microtensile bond strength (µTBS) between resin composite and erosively demineralised dentin. Materials and Methods:Dentin of 120 human molars was erosively demineralised using a 10-day cyclic de-and remineralisation model. For 40 molars the model comprised erosive demineralisation only, for anot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
1
12

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 24 publications
1
40
1
12
Order By: Relevance
“…Citric acid is the most often used demineralisation agent in studies of this kind, and the demineralisation durations were also chosen according to published research covering a wide range of demineralisation periods and of organic matrix thickness. The removal of the organic structures by collagenase solution has successfully been used in previous studies from different working groups [Ganss et al, 2004;Kato et al, 2012;Flury et al, 2013]. The collagenase is able to selectively remove the demineralised organic structures and does not remove additional mineral from the surface, as shown in a previous study [Ganss et al, 2009b].…”
Section: Discussionmentioning
confidence: 83%
“…Citric acid is the most often used demineralisation agent in studies of this kind, and the demineralisation durations were also chosen according to published research covering a wide range of demineralisation periods and of organic matrix thickness. The removal of the organic structures by collagenase solution has successfully been used in previous studies from different working groups [Ganss et al, 2004;Kato et al, 2012;Flury et al, 2013]. The collagenase is able to selectively remove the demineralised organic structures and does not remove additional mineral from the surface, as shown in a previous study [Ganss et al, 2009b].…”
Section: Discussionmentioning
confidence: 83%
“…It is conceivable that use of such a mouth rinse might have an influence on the bond strength of dentin adhesives applied on eroded dentin previously treated with this mouth rinse. In contrast to this assumption, it was shown that bond strength of resin composite and an MDP-containing self-etching adhesive (Clearfil SE Bond, Kuraray, Tokyo, Japan) to eroded dentin was not negatively influenced by the treatment with a tin-containing fluoride mouth rinse [71]. Further studies by the same group supported the hypothesis, that this effect might be due to a bond promoting capacity of the MDP-adhesive system to tincompounds in the dental hard tissue being present after use of the tin-containing fluoride mouth rinse [72,73].…”
Section: Erosively Altered Enamel and Dentin As Bonding Substratementioning
confidence: 84%
“…The incorporated tin might interfere with the adhesive applied during the following restorative procedure and thus impair the adhesion of the resin composite, reducing the longevity of the restoration. However, using an MDP-containing 2-step self-etching adhesive system (Clearfil SE Bond; Kuraray, Tokyo, Japan), bond strength to eroded dentine has been found not to decrease as a consequence of previous treatment with a tin-containing fluoride mouth rinse [13]. Indeed, bond strength increased.…”
Section: Erosive Tooth Wear and Adhesion Of Restorative Materialsmentioning
confidence: 98%
“…As a result of erosive processes dentine gradually becomes sclerotic, displaying a hypermineralized shiny surface along with tubular occlusion [6]. Although a few studies, using bovine dentine, have found no difference between resin bond strength to normal and sclerotic dentine [7,8], most studies, using human dentine, have reported bond strength to sclerotic dentine to be lower than the bond strength to normal dentine [4,[9][10][11][12][13]. The decrease is thought to result from the tubular occlusion by mineral salts, preventing resin tag formation [6].…”
Section: Erosive Tooth Wear and Adhesion Of Restorative Materialsmentioning
confidence: 98%